Informatics Open Library: Innovation in Developing Electronic- Service Case Study Departemen Informatics ITS - Mursidah, Eva; Qomariyah, Astutik Nur; Anggoro, Radityo (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2020)
Background of the study: Many of information resources available in the central library and Departemen Informatics of ITS, in various formats, printed, non- printed, electronic collections, and other media that require users to search for independent information, so users are faced with various search and location options.Purpose: This study aims to identify the problem of ability of library user to find the needs of information resources and Designing an integrated library information system in the Informatic Open Library application to solve user problems to find the needs of information resources. Method: This research uses qualitative approach with descriptive methods.Findings: Application development related to services and data security must continue to be done as well as analysis should be done every year by comparison with the analysis of the previous year to improve service quality at the highest level.Conclusion: Based on the results of research in the field, the implementation of the Informatic Open Library has been good, the aim of facilitating services for Siva ITS Department of Information has been achieved and provides benefits for lecturers. Librarian, education staff, students, and institutions. The role of librarians and librarian collaboration with lecturers and students is a supporting factor in the successful implementation of the Informatic Open Library application.